2015
DOI: 10.1093/hmg/ddv483
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital development in Pallister–Hall syndrome is disrupted in a cell-lineage-specific manner by constitutive expression of GLI3 repressor

Abstract: Pallister-Hall syndrome (PHS) is a rare disorder caused by mutations in GLI3 that produce a transcriptional repressor (GLI3R). Individuals with PHS present with a variably penetrant variety of urogenital system malformations, including renal aplasia or hypoplasia, hydroureter, hydronephrosis or a common urogenital sinus. The embryologic mechanisms controlled by GLI3R that result in these pathologic phenotypes are undefined. We demonstrate that germline expression of GLI3R causes renal hypoplasia, associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Our results are similar to the research on gain-or loss-of-functional mutants for Shh-Gli signaling [Cain et al, 2009[Cain et al, , 2011Haraguchi et al, 2012;Blake et al, 2016]. That research revealed that Shh-Gli signaling plays a major role in the metanephric collecting duct system during kidney and urogenital system development.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results are similar to the research on gain-or loss-of-functional mutants for Shh-Gli signaling [Cain et al, 2009[Cain et al, , 2011Haraguchi et al, 2012;Blake et al, 2016]. That research revealed that Shh-Gli signaling plays a major role in the metanephric collecting duct system during kidney and urogenital system development.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, deletion of both Gli3 and Shh rescues the renal phenotype observed in Shh conventional mutants as well as the expression of Pax2, Sall1, Cyclin D1, N-Myc, Gli1, and Gli2 [Gill and Rosenblum, 2006]. Inappropriate activation of the Shh-Gli signaling pathways occurs in several human cancers [Ok et al, 2012] and renal malformations [Pallister et al, 1989;Tsanev et al, 2009;McPherson and Cold, 2013;Blake et al, 2016]. Genetic elimination of Ptc1 in the ureteric cell lineage resulted in increased ectopic Shh signaling activity in the cortical collecting ducts and the UB tips of the developing kidney.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations